Interest rate liberalization and money market development : selected country experiences : proceedings of a seminar held in Beijing July/August 1995 - Mehran, Hassanali; Laurens, Bernard; Quintyn, Marc.; International Monetary Fund.; Chung-kuo jen min yin hang. (Washington, D.C : Monetary and Exchange Affairs Dept., International Monetary Fund, 1996)
This book presents the proceedings of a seminar on Interest Rate Liberalization and Money Market Development held in Beijing, China, in August 1995, sponsored by the Monetary and Exchange Affairs Department (MAE) of the International Monetary Fund together with the People's Bank of China (PBC)
Seminar sponsored by the Monetary and Exchange Affairs Department (MAE) of the IMF together with the People's Bank of China.
gau 02/08/16
Loans
Keywords: Interest rates; Money market; Capital market; Monetary policy; Securities industry